Restaurant O SIX JOINT Online Ordering System with Anti-SQL Injection - TANG, JIE YI; Nurul Hidayah Ab Rahman, (Applied Information Technology And Computer Science, 2021)
In the era advanced technology, e-commerce is becoming more popular all over the world including the food industry. Therefore, some restaurants have changed their traditional way of ordering food to an online ordering system. With the online ordering system, the operation of restaurants has become more efficient and it is convenient for customers to place an order quickly. In addition, online ordering also became a necessary condition for restaurants to survive, especially in the situation of coronavirus pandemic to reduce contact. However, the online ordering system is based on web service that has its own vulnerabilities such as SQL injection attacks. Therefore, an online ordering system which can minimize the risk called Restaurant O Six Joint Online Ordering system with Anti-SQL injection is proposed. The proposed system is developed in a web platform and adopts the Object-Oriented Software Development model as the methodology of this project. In this proposed system, the modules developed will be categorized for three target users which are user admins, staff and customers and another module which represents all of the target users. The significance of the project is to protect the web-based system from SQL injection attack by complying with the OWASP requirements. Moreover, other security mechanisms also implemented on the proposed system to achieve confidentiality, integrity, availability and authentication triad.